Frequência de brucelose bovina em rebanhos leiteiros e em seres humanos na região central do estado do Maranhão, Brasil - Carvalho, Robert Ferreira Barroso De; Santos, Hamilton Perreira; Mathias, Luís Antonio [UNESP]; Pereira, Hélder De Moraes; Paixão, Adriana Prazeres; Costa, Valter Marchão; Alves, Lúcia Maria Côelho (Instituto Biológico, 2016)
The aim of this study was to estimate the frequency of bovine and human brucellosis in the middle region of Maranhão. Thirty-five properties, registered at Maranhão State Agency of Agriculture Defense (AGED-MA), were chosen randomly, between May and October of 2013. Then, 525 blood serum samples from dairy cattle and 60 from milkers were serologically analyzed and went through an epidemiological questionnaire to investigate the risk factors associated to the infection. The diagnosis protocol used was the trial test of rose Bengal test (RBT), and the confirmation of reactors was by 2-mercaptoethanol (2-ME) and fluorescence polarisation assay (FPA). The frequency of animals that tested positive was 26/525 (4.95%) at RBT, and 17/525 (3.23%) and 13/525 (2.47%) at 2-ME and FPA, respectively. The frequencies of foci herds, with at least one positive animal, were 9/35 (25.71%) and 8/3 (22.85%), respectively. Regarding the milkers, 1/60 (1.66%) reacted at the confirmatory tests such as 2-ME, FPA and complement fixation. The risk factor, associated to brucellosis occurrence, in the multivariate analysis, was the presence of sheep (odds ratio - OR = 6.66, confidence interval - 95%CI = 1.26-35.03). The study showed that brucellosis is disseminated in the investigated dairy herd, indicating the need of a better control and eradication actions forbrucellosis in the examined region.

Objetivou-se com este estudo estimar a frequência da brucelose em bovinos e em ordenhadores na região central do Maranhão. Foram escolhidas, no período de maio a outubro de 2013, de forma aleatória, 35 propriedades cadastradas na Agência Estadual de Defesa Agropecuária do Maranhão (AGED-MA) e analisados sorologicamente 525 bovinos com aptidão leiteira, hemossoros de 60 ordenhadores, além de ter sido aplicado questionário epidemiológico para investigar os fatores de risco associados à infecção. O protocolo de diagnóstico utilizado foi o teste de triagem com antígeno acidificado tamponado (AAT), e a confirmação dos reagentes ocorreu mediante os testes 2-mercaptoetanol (2-ME) e polarização fluorescente (TPF). A frequência de animais sororreagentes foi de 26/525 (4,95%) no teste AAT e 17/525 (3,23%) e 13/525 (2,47%) nos testes de 2-ME e TPF, respectivamente. A frequência de rebanhos foco, com pelo menos um animal soropositivo, foi de 9/35 (25,71%) e 8/3 (22,85%), nessa ordem. Referente aos ordenhadores, 1/60 (1,66%) foi reagente nos testes confirmatórios de 2-ME, TPF e fixação de complemento. O fator de risco associado à ocorrência da brucelose, na análise multivariada, foi presença de ovinos (odds ratio - OR=6,66; intervalo de confiança de 95% - IC95% 1,26-35,03). O estudo demonstrou que a brucelose está disseminada no rebanho leiteiro investigado, indicando a necessidade de melhorias nas ações de controle e erradicação da brucelose na região estudada.
Frequency of brucellosis in bovine livestock dayre and humans in central region of the state of Maranhão, Brazil
Keywords: Brucella abortus; zoonoses; abortion; occupational disease; bursitis; Maranhão; Brucella abortus; zoonoses; aborto; doença ocupacional; bursite; Maranhão